2021
DOI: 10.1093/nar/gkab107
|View full text |Cite
|
Sign up to set email alerts
|

Role of CxxC-finger protein 1 in establishing mouse oocyte epigenetic landscapes

Abstract: During oogenesis, oocytes gain competence and subsequently undergo meiotic maturation and prepare for embryonic development; trimethylated histone H3 on lysine-4 (H3K4me3) mediates a wide range of nuclear events during these processes. Oocyte-specific knockout of CxxC-finger protein 1 (CXXC1, also known as CFP1) impairs H3K4me3 accumulation and causes changes in chromatin configurations. This study investigated the changes in genomic H3K4me3 landscapes in oocytes with Cxxc1 knockout and the effects on other ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
1
26
0
2
Order By: Relevance
“…Publicly available datasets were downloaded from Gene Expression Omnibus (GEO), including: H3K27me3 and H3K27ac ChIP-seq in GV oocytes, H3K4me3 ChIP-seq from d5 non-growing oocytes, d10 growing oocytes, d15 GV oocytes, d25 GV oocytes, Dnmt3 cDKO and Dnmt3 WT GV oocytes, and RNA-seq from Mll2 cKO and WT GV oocytes (GSE93941) ( 40 ), RNA-seq for GV oocytes (GSE70116) ( 46 ), RNA-seq from size-selected oocytes (GSE86297) ( 47 ), RNA-seq from Setd1b cKO and WT MII oocytes (GSE85360) ( 37 ), RNA-seq from Cxxc1 cKO and WT GV oocytes (GSE85019) ( 39 ), H3K4me3 ChIP-seq and bisulfite-seq from Cxxc1 cKO and WT GV oocytes (GSE159581) ( 48 ), and bisulfite-seq from d12 and d15 GV oocytes (GSE72784) ( 41 ). All raw data files were mapped and trimmed using the pipelines described above.…”
Section: Methodsmentioning
confidence: 99%
“…Publicly available datasets were downloaded from Gene Expression Omnibus (GEO), including: H3K27me3 and H3K27ac ChIP-seq in GV oocytes, H3K4me3 ChIP-seq from d5 non-growing oocytes, d10 growing oocytes, d15 GV oocytes, d25 GV oocytes, Dnmt3 cDKO and Dnmt3 WT GV oocytes, and RNA-seq from Mll2 cKO and WT GV oocytes (GSE93941) ( 40 ), RNA-seq for GV oocytes (GSE70116) ( 46 ), RNA-seq from size-selected oocytes (GSE86297) ( 47 ), RNA-seq from Setd1b cKO and WT MII oocytes (GSE85360) ( 37 ), RNA-seq from Cxxc1 cKO and WT GV oocytes (GSE85019) ( 39 ), H3K4me3 ChIP-seq and bisulfite-seq from Cxxc1 cKO and WT GV oocytes (GSE159581) ( 48 ), and bisulfite-seq from d12 and d15 GV oocytes (GSE72784) ( 41 ). All raw data files were mapped and trimmed using the pipelines described above.…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, the same authors demonstrated that in the absence of SETD1A/B in ESCs, H3K4me3 is maintained by MLL2, suggesting that these enzymes share some overlapping functions. The idea was further confirmed recently in mouse oocyte 48 …”
Section: Cfp1: a Regulatory Protein Found In Multiple Protein Complexesmentioning
confidence: 65%
“…The idea was further confirmed recently in mouse oocyte. 48 While each enzyme associates with a set of shared regulatory subunits that include WD Repeat 5 (WDR5), Retinoblastoma Binding Protein 5 (RbBP5), Acute Small Homeotic 2 Long (ASH2L), and Dumpy-30 (DPY-30), SETD1A/B also binds to WDR82 and CFP1. Loss of CPS40 (CFP1 yeast homolog) in yeast cells triggers a global loss of H3K4me3 with H3K4me2/me1 levels remaining relatively the same.…”
Section: Compass Complexes Regulating Histone H3k4 Tri-methylationmentioning
confidence: 99%
“…Therefore, we hypothesized that H3K4me3 these sets of promoters may have differing dependencies on H3K4 methyltransferases. To test this, we included publically available H3K4me3 ChIP-seq data for Cxxc1 cKO and Mll2 cKO GV oocytes (40,48). Globally, Setd1b cKO and Cxxc1 cKO GV oocytes show remarkably similar patterns of H3K4me3 (Supplementary Figure 4A, 4B, 4C), further supporting their co-dependence in the oocyte.…”
Section: Setd1b/cxxc1-deposited H3k4me3 Is Associated With Transcriptional Upregulation Of a Subset Of Oogenesis Genesmentioning
confidence: 88%
“…Publicly available datasets were downloaded from Gene Expression Omnibus (GEO), including: H3K27me3 and H3K27ac ChIP-seq in GV oocytes, H3K4me3 ChIP-seq from d5 non-growing oocytes, d10 growing oocytes, d15 GV oocytes, d25 GV oocytes, Dnmt3 cDKO and Dnmt3 WT GV oocytes, and RNA-seq from Mll2 cKO and WT GV oocytes (GSE93941) (40), RNA-seq for GV oocytes (GSE70116) (46), RNA-seq from size-selected oocytes (GSE86297) (47), RNA-seq from Setd1b cKO and WT MII oocytes (GSE85360) (37), RNA-seq from Cxxc1 cKO and WT GV oocytes (GSE85019) (39), H3K4me3 ChIP-seq and bisulphite-seq from Cxxc1 cKO and WT GV oocytes (GSE159581) (48), and bisulphite-seq from d12 and d15 GV oocytes (GSE72784) (41,42). All raw data files were mapped and trimmed using the pipelines described above.…”
Section: Publicly Available Datasetsmentioning
confidence: 99%